From Motif to Meaning: Digital Batik Storytelling and Brand Identity in Indonesia - Arus Reka Prasetia; Muhammad Firdaus Benyamin (Indonesian Scientific Publication, 2026)
Indonesian batik brands increasingly use Instagram and official websites to circulate heritage narratives, motif references, and commercial collections. However, the cross-platform process through which motif references become coherent brand meaning remains insufficiently specified, particularly in relation to arts management and cultural stewardship. This study introduces motif-to-meaning translation as a conceptual lens for explaining how motif references in brand-authored digital artefacts are connected to communicated identity claims across websites and Instagram. Using a qualitative multiple-case digital artefact analysis, the study examined 150 official artefacts from five Indonesian batik brands, comprising 25 website pages and 125 Instagram posts and reels published between 1 January 2024 and 1 October 2025. The analysis showed that Instagram was dominated by campaign-led storytelling and episodic heritage narration, whereas websites more often anchored institutional legitimacy, heritage explanation, formal documentation, and sustainability commitments when present. Across the corpus, motifs were translated into meaning through recurring narrative moves that linked motif references to value statements, lifestyle framing, participatory invitations, and craft-process legitimacy. The five brands also differed in their communicated identity profiles, reflected in distinct configurations of heritage legitimacy, craft authority, market-facing identity, and responsibility cues. The findings suggest that coherent digital batik communication depends on coordinated curation and interpretive governance across platforms, highlighting platform strategy as a salient concern for arts management.